Gender and Transnational Plant Scientists : Negotiating Academic Mobility, Career Commitments and Private Life - Pettersson, Helena (My University, 2011)
The aim of the article is to analyze how gender intersects with mobility, career and private life among a highly transnational group of researchers, namely plant scientists. The author’s hypothesis is that academic mobility and science are constituted with gender as an important incentive. The study is based on ethnographic field work such following observations and in depth interviews with researchers in plant science. The plant scientists work at an international science center in Sweden with co-workers from 35 different countries. Using the concept of “capital”, the relationship between mobility, career and gender is problematized. Furthermore, the article will look at the informants’ work-life balance, i. e. how scientists manage academic mobility in relation to their private lives.
Keywords: academic capital; Academic mobility; career; Gender; Karriere; private life; Vereinbarkeit; ddc:300